The end of the 3rd millennium BC in the Levant: new perspectives and old ideas. (2nd January 2016) - Kennedy, Melissa A.
Abstract : The end of the 3rd millennium BC in the Levant has been interpreted as a time of settlement collapse and dislocation. A variety of theories have been proposed to account for this, such as climate change and landscape degradation, natural disaster and population movements. This article will review the archaeological evidence for this period in the Levant and offer new insights into what potentially occurred at the end of the 3rd millennium BC.